Immunology of malaria. Current status - Herrera Valencia, Sócrates; Arevalo de Herrera, Myriam (Colombia Medica, 1987)
Malaria is a parasitic disease caused by microorganisms of the Plasmodium genus and transmitted by mosquitoes of the Anopheles genus. It is the most critical parasitic entity in the tropics; its transmission occurs in more than 100 countries in Africa, Central and South America, Asia, and Oceania, in addition to Mexico, Haiti, Dominican Republic, and Turkey, where more than 2.6 billion inhabitants are at risk of acquiring the infection.